Activated and Nonactivated Date Pits Adsorbents for the Removal of Copper(II) and Cadmium(II) from Aqueous Solutions. (9th December 2012) - Hilal, Nora M.; Ahmed, Inas A.; El-Sayed, Ragaa E.
Abstract : The present study aims to investigate the adsorption behavior of Cu(II) and Cd(II) ions from wastewater onto low-cost adsorbents either raw date pits (RDP), cheap agricultural and nontoxic materials, or chemically activated carbon (ADP) prepared by modified date pits using phosphoric acid. A series of experiments were conducted in a batch system to evaluate the effect of system variables. The adsorption process is affected by various parameters such as solution pH, contact time, initial concentrations of metals, and adsorbent dose. The optimum pH required for maximum adsorption was found to be 5.8 ± 0.5 . The experimental data were tested using Langmuir, Freundlich, Dubinin-Radushkevich (D-R) isotherm equations. It was observed that the adsorption capacity of date pits increased after treatment with phosphoric acid. The maximum uptake capacities (Q m ) were 7.40 and 33.44 mg copper(II) per gram of RDP and ADP, respectively, while 6.02 and 17.24 mg cadmium(II) per gram of RDP and ADP, respectively. The results showed that although the equilibrium data could be described by the three models used, Langmuir model gave slightly better results while Freundlich model gave better results when using raw and activated date pits.